Modified ethylene/α‐octene co‐polymer composites based on dual toughening of hydrogen bonding network and nanospheres. (6th April 2022) - Huang, Zhiyi; Liao, Tingting; Liu, Xiaochun; Wu, Jianyu; Tang, Zilun; Pan, Guoyi; Liu, Huameng; Lin, Xiaofeng; Lin, Wenjing; Li, Yong; Gu, Yuxin; Yi, Guobin
Abstract: Thermoplastic elastomer ethylene/α‐octene co‐polymer (POE) is a special polymer material with both elasticity and thermoplasticity. However, the nonpolarity and low‐tensile strength of POE limit its application in polar materials and high‐strength materials fields. In this study, we synthesized a specific molecule with C═C bonds and NH bonds, which was introduced into POE to construct hydrogen bonding network, and the prepared modified POE is further blended with carboxyl terminated polystyrene nanospheres as toughening agent to prepare modified POE elastomer composites. Based on such dual toughening strategy containing chemical modification and physical toughening, the modified POE elastomer composites possess improved mechanical properties. The composites achieve a tensile strength of 21.4 MPa, elongation at break of 1268%, fracture energy of 109.6 MJ∙m −3 and exhibit improved thermal stability. Impressively, the tensile strength of reprocessed composites is restored to more than 90% of their original tensile strength even after four times of reprocessing steps, demonstrating excellent reusability.